Electronic bandstructure and van der Waals coupling of ReSe2 revealed by high-resolution angle-resolved photoemission spectroscopy - Lewis S. Hart (Nature Portfolio, 2017)
Abstract ReSe2 and ReS2 are unusual compounds amongst the layered transition metal dichalcogenides as a result of their low symmetry, with a characteristic in-plane anisotropy due to in-plane rhenium ‘chains’. They preserve inversion symmetry independent of the number of layers and, in contrast to more well-known transition metal dichalcogenides, bulk and few-monolayer Re-TMD compounds have been proposed to behave as electronically and vibrational decoupled layers. Here, we probe for the first time the electronic band structure of bulk ReSe2 by direct nanoscale angle-resolved photoemission spectroscopy. We find a highly anisotropic in- and out-of-plane electronic structure, with the valence band maxima located away from any particular high-symmetry direction. The effective mass doubles its value perpendicular to the Re chains and the interlayer van der Waals coupling generates significant electronic dispersion normal to the layers. Our density functional theory calculations, including spin-orbit effects, are in excellent agreement with these experimental findings.